2006
DOI: 10.1016/j.jacc.2006.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pulmonary Arterial Hypertension With the Selective Endothelin-A Receptor Antagonist Sitaxsentan

Abstract: Treatment with the selective ET(A) receptor antagonist sitaxsentan, orally once daily at a dose of 100 mg, improves exercise capacity and WHO FC in PAH patients, with a low incidence of hepatic toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
279
0
20

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(305 citation statements)
references
References 15 publications
6
279
0
20
Order By: Relevance
“…The critical role of ET-1 in PH has been largely demonstrated [20][21][22], underlying the now widely used therapeutic strategies in idiopathic PH based on ET-1 receptor blocking either dually [33,34] or specifically directed to ETAR [35]. Very few data other than increased ET-1 levels in serum [18] and in sputum [19] of CF patients exist as to a potentially pathogenic role of ET-1 in CF.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of ET-1 in PH has been largely demonstrated [20][21][22], underlying the now widely used therapeutic strategies in idiopathic PH based on ET-1 receptor blocking either dually [33,34] or specifically directed to ETAR [35]. Very few data other than increased ET-1 levels in serum [18] and in sputum [19] of CF patients exist as to a potentially pathogenic role of ET-1 in CF.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,60 In clinic, efficacy and safety of endothelin-receptor antagonist has been confirmed in PAH patients. [61][62][63][64] Because ET-1 (upregulated in PAH) activates NFATc1, which in turn increases bcl ¡ 2 expression, contributing to the prosurvival and antiapoptotic effects of ET-1, 65 endothelin-receptor antagonist might also inhibit NFAT activation. At present, most of studies found that interventions targeting NFAT pathway may be effective for PAH therapy.…”
Section: Targeting the Nfat Pathway For Pah Therapymentioning
confidence: 99%
“…These drugs can improve the cardiac and pulmonary pressures as well as exercise capacity. [15][16][17] …”
Section: Endothelin-1 Receptor Antagonistsmentioning
confidence: 99%